1997
DOI: 10.1002/(sici)1097-4598(199712)20:12<1487::aid-mus2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of thyroid state and denervation on skeletal myosin heavy chain expression

Abstract: The goal of this study was to examine the effects of altered thyroid state and denervation (Den) on skeletal myosin heavy chain (MHC) expression in the plantaris and soleus muscles. Rats were subjected to unilateral denervation (Den) and randomly assigned to one of three groups: (1) euthyroid; (2) hyperthyroid; (3) and hypothyroid. Denervation caused severe muscle atrophy and muscle‐type specific MHC transformation. Denervation transformed the soleus to a faster muscle, and its effects required the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 40 publications
5
46
0
4
Order By: Relevance
“…The fiber type transformation seen in rabbit muscles did not differ from that in rat muscles examined at an earlier stage of denervation (5,23,25,34,56,59). In one of those studies, coexpression of the different isoforms showed that the switch occurred within individual fibers and not by replacement with fibers of another type (34).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The fiber type transformation seen in rabbit muscles did not differ from that in rat muscles examined at an earlier stage of denervation (5,23,25,34,56,59). In one of those studies, coexpression of the different isoforms showed that the switch occurred within individual fibers and not by replacement with fibers of another type (34).…”
Section: Discussionmentioning
confidence: 58%
“…The mass of the affected muscles falls rapidly within 5-7 days of axotomy (11,18,22,25,55,57,58) and declines further to 30 -50% of control weight in succeeding weeks (1,5,11,14,23,41,60). After several months, muscle weight stabilizes at ϳ5-20% of control (1,13,45).…”
mentioning
confidence: 98%
“…Thyroid hormones act by repressing or activating the genes coding for the different myosin isoforms, and all members of the MyHC multigene family respond to changes in 3,5,3Ј-triiodo-L-thyronine (T 3 ) levels, although the mode of response is determined in a highly muscle and fiber type-specific manner (20,40). Both fast-and slow-twitch muscles respond rapidly to both hyper-and hypothyroidism at the MyHC mRNA level (1,2,4,10,14,20). The response at the protein level is slower and partially different from that at the mRNA level.…”
mentioning
confidence: 99%
“…They typically function as weight-bearing and postural muscles. In the soleus, a slow muscle in the hindlimb, ϳ90% of fibers express the ␤-form of MHC (13,16). The relationship between weight-bearing activity and the expression of ␤-MHC in soleus muscle is demonstrated by removing the factor of load in experimental animal models.…”
mentioning
confidence: 99%